Perioperative kinetics of endocan in patients undergoing cardiac surgery with and without cardiopulmonary bypass. (July 2016) - Madhivathanan, Pradeep R.; Fletcher, Nick; Gaze, David; Thomson, Rebekah; Chandrasekaran, Venkatachalam; Al-Subaie, Nawaf; Valencia, Oswaldo; Sharma, Vivek
Abstract: Introduction: Endothelial Specific Molecule-1 or endocan is a novel biomarker associated with the development of acute lung injury (ALI) in response to a systemic inflammatory state such as trauma. Acute Respiratory Distress syndrome (ARDS), a severe form of ALI is a devastating complication that can occur following cardiac surgery due to risk factors such as the use of cardiopulmonary bypass (CPB) during surgery. In this study we examine the kinetics of endocan in the perioperative period in cardiac surgical patients. Methods: After ethics approval, we obtained informed consent from 21 patients undergoing elective cardiac surgery (3 groups with seven patients in each group: coronary artery bypass grafting (CABG) with the use of CPB, off-pump CABG and complex cardiac surgery). Serial blood samples for endocan levels were taken in the perioperative period (T0: baseline prior to induction, T1: at the time of heparin administration, T2: at the time of protamine, T2, T3, T4 and T5 at 1, 2, 4 and 6 h following protamine administration respectively). Endocan samples were analysed using the enzyme-linked immunosorbent assay (ELISA) method. Statistical analysis incorporated the use of test for normality. Results: Our results reveal that an initial rise in the levels of serum endocan from baseline in all patients after induction of anaesthesia. Patients undergoing off-pump surgery have lower endocan concentrations in the perioperative period than those undergoing CPB. Endocan levels decrease following separation from CPB, which may be attributed to haemodilution following CPB. Following administration of protamine, endocan concentrations steadily increased in all patients, reaching a steady state between 2 and 6 h. The baseline endocan concentrations were elevated in patients with hypertension and severe coronary artery disease. Conclusion: Baseline endocan concentrations are higher in hypertensive patients with critical coronary artery stenosis. Endocan concentrations increased after induction of anaesthesia and decreased four hours after separation from CPB. Systemic inflammation may be responsible for the rise in endocan levels following CPB.